POTENSI TUMBUHAN OBAT DI CAGAR ALAM DOLOK SAUT, DESA PANSUR NATOLU, KECAMATAM PANGARIBUAN, KABUPATEN TAPANULI UTARA - Marjuki Sihombing; Irawati Azhar; Yunus Afifuddin (Peronema Forestry Science Journal, 2016)
Dolok Saut Preserve as a part of protected forest has many forest products potency, especially medical plants. However, data of medical plants that grow in the preserve had not been documented, so that need to be done of research to analyze the biodiversity and potential of medical plants in Dolok Saut Preserve. The purpose of the research was to know the potential and biodiversity of medical plants in Dolok Saut Preserve. The research had been done in November 2015 to December 2015. The method that used is purposive sampling plots with 20x20 meter square width. The species and the quantity of medical plants that found at preserve was identified.The result of medical plants biodiversity showed 12 species of medical plants. The biodiversity of medical plants in Dolok Saut Preserve at undergrowth stafe was 2,07, seedling stage was 0,23, saplings stage was 0,43, poles stage was 0,38, and trees stage was 0,58. Keywords : biodiversity, Dolok Saut Preserve, medical plants